Mitochondria-Associated Endoplasmic Reticulum Membranes in Microglia: One Contact Site to Rule Them all - Elisa Navarro; Jorge Montesinos (Contact)
Microglia, the resident immune cells of the central nervous system (CNS), play a crucial role in maintaining tissue homeostasis by monitoring and responding to environmental changes through processes such as phagocytosis, cytokine production or synapse remodeling. Their dynamic nature and diverse functions are supported by the regulation of multiple metabolic pathways, enabling microglia to efficiently adapt to fluctuating signals. A key aspect of this regulation occurs at mitochondria-associated ER membranes (MAM), specialized contact sites between the ER and mitochondria. These structures facilitate the exchange of calcium, lipids, and metabolites and serve as metabolic and signaling hubs. This review synthesizes current research on how MAM influence microglial physiology, with an emphasis on their role in immunometabolism, offering new insights into the integration of metabolic and immune functions in the CNS and its impact in the context of neurodegeneration.